Pengaruh Magang Kewirausahaan Terhadap Intensi Berwirausaha Mahasiswa Melalui Sikap Kewirausahaan Sebagai Variabel Intervening di Universitas Negeri Jakarta - Pradita Genuineta Santoso; Agus Wibowo; Ari Saptono (Indo Publishing, 2026)
This study aims to analyze the influence of entrepreneurial internships on students' entrepreneurial intention through entrepreneurial attitude as an intervening variable. The study was motivated by the relatively low level of students' entrepreneurial intention despite the implementation of various entrepreneurial internship programs in higher education, as well as the importance of fostering entrepreneurial attitudes to encourage students to choose entrepreneurship as a career path. This research employed a quantitative approach using a survey method. The research sample consisted of 239 respondents who were students of Universitas Negeri Jakarta and had participated in entrepreneurial internship programs. The respondents were selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that entrepreneurial internships have a positive and significant effect on both students' entrepreneurial intention and entrepreneurial attitude. Entrepreneurial attitude also has a positive and significant effect on students' entrepreneurial intention. Furthermore, entrepreneurial attitude partially mediates the relationship between entrepreneurial internships and students' entrepreneurial intention. These findings suggest that improving students' entrepreneurial intention can be achieved through the implementation of high-quality entrepreneurial internship programs, the development of positive entrepreneurial attitudes, and the provision of practical experiences that enhance students' readiness to become entrepreneurs. This study contributes to the entrepreneurship literature, particularly regarding the role of entrepreneurial internship experience in shaping entrepreneurial intention through entrepreneurial attitude, and provides valuable insights for higher education institutions in designing more effective entrepreneurial internship programs to foster the emergence of young entrepreneurs.